PLS-SEM: A hidden gem in tourism research methodology - Seočanac, Marijana (Hotel and Tourism Management, 2024)
Purpose – The main objective of this paper is to provide a well-organized guide for the application of partial least squares structural equation modeling (PLS-SEM) in tourism research. In this way, the paper strives to encourage future tourism studies to use PLS-SEM and contribute to methodological advances in the field. Methodology – This paper systematically examines the application of PLS-SEM with a particular focus on the application of hierarchical constructs in tourism research and carefully analyzes and classifies the existing literature on PLS-SEM. Results – Specific steps for evaluating and interpreting the hierarchical latent variables of the PLS model are presented and explained. Implications – This paper contributes to advancing the application of PLS-SEM in tourism research by providing researchers with a valuable tool to improve both the rigor of empirical investigation and theoretical development in the field. The insights gained from this paper can guide subsequent research to investigate specific tourism-related scenarios, potentially leading to new transformative discoveries and paradigm shifts in our understanding of tourism dynamics.